Loom as an innovative tool to enhance english speaking skills through the creation of e-portfolios - Franco-Bayas, Miguel A.; Sandoval-Pérez, Maria J.; Contreras-Moscol, Daniel (Dominio de las Ciencias, 2020)
Technology is becoming essential in both the daily and complex tasks of humanity. Education is also being benefited by technological advances at the service of the teacher as is the case of the e-portfolio. This article presents the case study of the use of e-portfolios in English subjects in a University of Babahoyo; the objective is to reflect on students' perception regarding their use, complemented by the Loom tool. The literature review section discusses the current status of the e-portfolio from a technological and educational perspective. Typologies and characteristics of e-portfolios are commented on, and finally case studies of researchers and the conclusions they have reached are cited. The methodology in this article has a descriptive approach through a questionnaire taken from 54 students. The results mention that the respondents showed their acceptance for the realization of the e- portfolio as an aid to their teaching process - learning English and in their technological skills. In addition, the importance of teacher mentoring and accompaniment in this process is recognized. It also highlights how challenging it was to learn and apply the web tool Loom for the development of the e-portfolio, but there is a promising future at the professional level by learning this type of Tics tools. It is concluded that the e-portfolios promise direct benefits to the students in an academic and professional way, without forgetting that the availability to these tools would facilitate to the teacher as to the student its application.